Avaliação de uma intervenção em bullying envolvendo alunos, professores e pais - Valle, Jéssica Elena (2021)
Due to the need for effective interventions to combat bullying, researchers currently recommend programs with a whole-school approach, using multiple strategies to work with different individuals in the school context. Therefore, the main objectives of this thesis were the development, pilot test, and evaluation of a whole-school antibullying intervention program involving students, teachers, and parents. Based on these objectives, three studies were conducted and are presented as scientific texts. In the first study, a literature review with a detailed description of the main components used in whole-school antibullying intervention programs is presented. Based on the analysis of 17 publications, it was noted that the components most used in whole-school antibullying programs included: teacher or school staff training; classroom activities for students; informational materials for parents; informational materials for teachers or school staff; antibullying committee; and specific interventions for students involved in bullying. In the second study, the development, pilot test, and evaluation of a whole-school antibullying intervention program involving students, teachers, and parents in the Brazilian context are presented. Participants included 11 students from a 5th grade class at a public school in the state of São Paulo, Brazil, as well as 13 teachers from the same school. Informational materials about bullying were sent to the parents. Before and after the intervention program, the School Violence Scale was applied. In addition, the participants evaluated each intervention session and the intervention as a whole. When comparing pre-test and post-test data, a significant reduction in bullying victimization and in identification of bullying episodes by teachers was observed. However, no significant results were found regarding bullying perpetration, reporting bullying occurrences, and perception of intervention by third-parties in bullying episodes, nor regarding knowledge, intervention, and perception of teachers’ self-efficacy in responding to bullying. In the third study, the evaluation of a whole-school antibullying intervention for students, teachers, and parents is presented, in terms of apparent (or face) and content validity. Participants included eight professionals, who each evaluated one of the modules. Agreement among judges was 100% for the Student Module, 100% for the Teacher Module, and 45% for the Parent Module of the proposed intervention. These results support the adequacy of the modules for students and teachers, but the module for parents need to be revised. The results of these three studies reinforce the importance of bullying interventions based on a whole-school approach, to encompass the complexity of the phenomenon and to facilitate significant effects in reducing this problem. In addition, detailed information about components of antibullying intervention programs is important to choose between replicating existing programs or developing new ones, as well as to compare effects among programs. Finally, it is important to underscore the need for such programs to be developed in partnership with government and school representatives, to include the components most suitable to the context in which they will be used, considering demands, resources, and limitations.